The mobility assessment course: A ready‐to‐use dynamic measure of visuospatial neglect. Issue 3 (20th April 2022) - Nelemans, Katinka N.; Nijboer, Tanja C. W.; Ten Brink, Antonia F.; ,
Abstract : The Mobility Assessment Course (MAC) is a tool to measure visuospatial neglect in a dynamic fashion. Although the MAC has been shown to dissociate between patients with and without neglect, it remains unclear whether it is applicable in clinical settings. We evaluated the MAC regarding its (1) feasibility as a diagnostic tool as part of standard care, (2) construct validity, and (3) underlying constructs and potential confounders. A consecutive sample of stroke patients admitted to inpatient rehabilitation completed the MAC, shape cancellation, line bisection, and/or Catherine Bergego Scale (CBS) as part of the standard assessment. To assess feasibility, we computed the percentage of patients who completed the MAC. Construct validity was tested by evaluating MAC performance between patients with and without neglect and controls. Finally, a regression analysis was conducted to assess underlying constructs and potential confounders of MAC performance (i.e., level of mobility and lesion side). The MAC was completed by 82% of patients ( N = 182/223; of whom 145 completed all tasks). Patients with neglect performed worse on the MAC (indicating more severe neglect) compared to patients without neglect and controls. The MAC had a lower sensitivity and higher specificity than paper‐and‐pencil tasks and the CBS. Performance on shape cancellation, line bisection, and CBS were predictors of MAC performance. Level of mobility and lesion side did not predict MAC scores, indicating that these factors do not confound its reliability. To conclude, the MAC is an easy‐to‐implement tool to evaluate neglect in a dynamic manner, which can be administered in addition to conventional paper‐and‐pencil tasks.